The seasonal distribution of savannah elephants (Loxodonta africana africana) in Nazinga Game Ranch, southern Burkina Faso - Hema, Emmanuel; Barnes, Richard; Guenda, Wendengoudi (Pachyderm, 2020)
Elephant wet and dry season distributions were compared at Nazinga Game Ranch in southern Burkina Faso. Dropping counts along line transects provided an index of occupancy at the end of each season: wet 2006, dry 2007 and dry 2008. We expected that the distribution of elephants would differ between the dry and the wet seasons, with elephants concentrating around water sources in the dry season and spreading out across the landscape during the wet season. Elephants were found to be clumped in both wet and dry seasons, although the degree of aggregation was much greater in the dry seasons, especially in the drier year of 2008. Human populations have increased dramatically around Nazinga in the last 15 years, and we speculate that the increasing abundance of crops outside in the wet season may influence the distribution of elephants inside the ranch area. Key words: Nazinga, Burkina Faso, elephants, distribution, wet season, dry season Les distributions d’éléphants des saisons pluvieuse et sèche, ont été comparées au Ranch de Gibier de Nazinga. L’indice d’occupation des éléphants dans le ranch à été estimé au moyen des mesures de déjections le long des transects, en fin de saison pluvieuse 2006 et en fin de saisons sèches 2007 et 2008. Les attentes étaient que la distribution des éléphants en saison sèche soit différente de celle de la saison pluvieuse; avec un regroupement des éléphants autour des points d’eau en saison sèche, puis leur dispersion dans les paysages de toute l’aire du ranch pendant la saison pluvieuse. Il a été observé que les éléphants étaient regroupés aussi bien en saison sèche qu’en saison pluvieuse; même si le degré d’agrégation était plus important en saison sèche particulièrement en 2008 qui était l’année la plus sèche. La densité des populations humaines a augmentée considérablement autour de Nazinga, pendant les 15 dernières années; nous soupçonnons que la disponibilité des cultures hors du ranch pendant la saison pluvieuse, pourrait influencer la distribution des éléphants à l’intérieur du ranch.